Intracolonic Mustard Oil Induces Visceral Pain in Mice by TRPA1-Dependent and -Independent Mechanisms: Role of Tissue Injury and P2X Receptors - Rafael Gonzalez-Cano; Rafael Gonzalez-Cano; Rafael Gonzalez-Cano; Ángeles Montilla-García; Ángeles Montilla-García; Gloria Perazzoli; Jesús M. Torres; Jesús M. Torres; Francisco J. Cañizares; Francisco J. Cañizares; Eduardo Fernández-Segura; Eduardo Fernández-Segura; et al. (Frontiers Media S.A., 2021)
Both TRPA1 and purinergic P2X receptors have been proposed as potential targets for the treatment of visceral pain. We found that the intracolonic administration of a low dose mustard oil (0.5%), a well-known TRPA1 agonist, produced nociceptive responses and abdominal wall referred mechanical hyperalgesia, without inducing apparent tissue damage. Both nociceptive responses and referred hyperalgesia were abolished by the ablation of TRPV1-expressing neurons (and the consequent ablation of TRPA1+ nociceptors) by resiniferatoxin (RTX) treatment, and by the TRPA1 antagonist AP18. However, a higher dose of mustard oil (2.5%) damaged the colonic epithelium and induced pERK activation in the spinal cord, and these processes were clearly independent of TRPV1-expressing neurons ablated by RTX. This higher dose of mustard oil induced nociceptive responses and referred mechanical hyperalgesia which were insensitive or only slightly sensitive to resiniferatoxin or AP18, but were markedly reduced by the P2X antagonist TNP-ATP, which is known to inhibit nociceptive actions induced by ATP released from injured tissues. In conclusion, whereas a low dose of intracolonic mustard oil induces visceral pain in a manner fully dependent on TRPA1 actions, when a high dose of this chemical irritant is used, visceral pain becomes mostly independent of TRPA1 activation but clearly enhanced by ATP purportedly released by the damaged colonic epithelium. Therefore, TRPA1 inhibition is not sufficient to substantially decrease visceral pain during tissue injury, whereas purinergic antagonism appears to be a more effective strategy.